IMPLEMENTASI PERATURAN BUPATI SRAGEN NOMOR 22 TAHUN 2014 TENTANG PELAYANAN ADMINISTRASI MASYARAKAT DESA DAN KELURAHAN (PADMA) KABUPATEN SRAGEN - Sri Riris Sugiyarti, Yhoga Ayuningtyas, Joko Pramono & (Transformasi, 2016)
The Sragen Major Rule No. 22 in 2014 year concerning in the service of Administration ofvillage has a purpose for ineceasing the quality of effectively, efficiently serving and make theserving as well as the villagers needs. It has a benefit in issuing the birth certificate or civiladministration, permit, and non permit. It makes the definitive villagers data and does not makedouble data whwen it is issued. The theory which is issued for supporting the implementedanalysis of the serving of administration of village (PADMA). Eivils policy is implemented modelpolicy which is improved by Van Metter and Van Horn. The research Method which is used isqualitative research, there for the researcher chooses the informan by using purposive samplingand snowball. The researcher uses the technique of collecting data which is combination of sometechnique, namely, literature, interview, straight observation and documentation. The researchhas a conclusion that is the implementation of the Major Policy concerning in service ofAdministration of Villagers (PADMA) has been done it has several laek of implementation,because of human resourches of civil servant who works in Karangjati office be unable to give acivil service effetively and efficiently. There are not awareness for taking their ownadministration and the lack of sosialitation to the villagers that cause of misunderstanding anddis informating received.Keywords: Implementation, Policy, Serving, Administration.